Chromosome studies related to fertility in crossbred buffaloes in Malaysia. - Bongso, T. A.; Hilmi, M.; Jainudeen, M. R. (1982)
Chromosome analysis was undertaken on Murrah, Swamp, F1 crossbred (Murrah x Swamp) and first generation backross (F1 female x Murrah male) buffaloes using the leukocyte culture method combined with Giemsa (G) and centromeric (C) and nucleolar organiser region (NOR) banding procedures. The F1 crossbred had a diploid chromosome complement(2n=49)intermediate to its two parents (Murrah,2n=50 ; Swamp, 2n=48). Two backross animals were 2n=49 and 2n=50 respectively. Construction of G,C NOR and conventional karyotypes revealed that the largest two metacentric chromosome in the Swamp buffalo resulted from a telomere-centromere tandem fusion between chromosomes 4p and 9 of the Murrah karyotype. The F1 crossbred and backross animals with 2n=49 showed a similar tandem fusion, occuring however between one member each of chromosome pairs 4p and 9. The two X chromosome (acrocentric) in female buffaloes had large masses of centromeric heterochromatin and one pair of dark bands in their arms proximal to the centromere, while in the Y chromosome of males, centromeric heterochromatin was not stained. The Y chromosome was not the smallest chromosome in the buffalo karyotype. The implications of the 2n=49 chromosome complement on fertility via inter se and backcross matings is hypothesised and discussed.